(Re)creating a living memorial: urban gardening as a multispecies co-creating practice - Niala, JC (Universidad de Alcalá, 2023)
This essay explores what happened when I recreated an allotment in the style of the year 1918. The plot was located on a charity allotment site in the city of Oxford in the United Kingdom and cultivated during the growing season of 2020 to2021. There have been people growing on the site for over a century. I planted open pollinated non-hybrid heritage seeds from the era. Reflecting on the use of landscape as an archive, I use both academic and creative responses to the soil as a repository of memory. The plot itself became a living memorial that diverse members of the public visited, to share food and engage with the plot and the themes it generated. These themes were the current COVID-19 pandemic, the 1918/1919 flu pandemic, and the First World War in Africa and Europe. In contrast to contested public memorials, the allotment garden space facilitated restoration. This essay therefore examines what can be enabled through a co-creating a multispecies gardening practice. It discusses whether the inclusion of nature enables a different engagement with challenging histories. By working with a store of memory within the natural world, the case study of the 1918 allotment demonstrates the ways in which it is possible to transcend both time and space, to open up counter narratives of key periods in global history. The 1918 allotment also offers up a methodological approach that works with the practice of decolonisation as “convivial” (Nyamnjoh). A meeting place for varied peoples and more-than-human others to come together in transformation, through urban gardening and working alongside and with more-than-human gardeners.